Logistical analysis of pharmaceutical assistance in a northeast brazilian hospital - Gomes, Amanda Brisa de Sousa (2020)
This study aims to analyze the logistics of pharmaceutical care of a hospital in northeastern Brazil. The research is quantitative and qualitative, retrospective and concurrent exploratory. The study was conducted at the Manoel de Sousa Santos Regional Hospital, located in the municipality of Bom Jesus, Piauí, which serves 13 municipalities. The collection period occurred from June to July 2019, and was developed through a questionnaire about each stage of the pharmaceutical logistics cycle employed in the pharmacy. A descriptive and qualitative analysis of the pharmaceutical care cycle process was elaborated, in which the main points of relevance and improvements were observed. With this, it was identified through frames, the main points of each stage of the cycle. Its main results are deficiencies in the stages of the pharmaceutical care cycle, which may lead to problems related to patient treatment. It was found that the Hospital does not have a Pharmacy and Therapeutic Committee and that medication dispensing is usually done by a nursing technician. The hospital where the study was conducted is not in compliance with all stages of the pharmaceutical care cycle, due to the lack of 24hrs pharmacist, which can lead to Drug-related Problems, as the pharmacist is responsible for analyzing prescriptions and monitoring pharmacotherapeutic agent, which guarantees safety and efficacy for the treatment of the patient. Only through rigorous evaluation of all stages of the pharmaceutical care cycle can qualified drug access be provided.